The Feedback Effects of Controversial Police Use of Force - Mullinix, Kevin J.; Bolsen, Toby; Norris, Robert J. (Political behavior, 2021)
Controversial cases of police use of force against minority civilians have become a ubiquitous feature of news headlines, and videos of these interactions between citizens and government actors have placed them in the public sphere. In this paper, we examine the feedback effects of these publicized incidents. Using a unique survey-experiment implemented in 2019, we demonstrate that controversial police use of force against minority civilians prompts strong emotional reactions, increases support for body-cameras, changes beliefs about excessive force, and alters attitudes toward law enforcement. Notably, our design allows us to examine the effects of both text-based news stories and videos pulled from two real-world use of force cases, one lethal and one non-lethal. This study has important implications for public opinion, feedback effects, and perceptions of law enforcement.